Perceraian Dalam Fiqh Mazhab Dan Sistem Peradilan - Ahmad Habib Dairobi; Muhammad Amar Adly (KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to discuss the concept of marriage dissolution from the perspective of the four schools of fiqh, namely Hanafi, Maliki, Shafi'i and Hanbali. This research focuses on the legal comparison of divorce as the main form of marriage dissolution by analyzing the harmony between the views of fiqh and positive law in Indonesia, such as Law No. 1 of 1974 and the Compilation of Islamic Law. The method used is a literature review with a qualitative approach, where data is collected from classical books, the Qur'an, Hadith, and legal documents. The results of this study show that the breakdownof marriage can occur in various forms, including divorce, fasakh, khulu', li'an, and zhihar, although divorce is the main focus due to its prevalence. The four madhhabs are similar in the basic principles of divorce, but differ in details such as the conditions, pillars, and categories of divorce. The research also notes that the ruling on divorce can vary from permissible, makruh, haram, sunnah, or wajib depending on the context. This research provides a deeper insight into the complexity of Islamic law regarding the dissolution of marriage, which is relevant to the legal needs of modern society as well as the application of Shari'a in the national legal system.